Dengue Shock Syndrome – A Case Report - P, Sharmila Nirojini; V, Durga; S, Dahlia Dixcy; J, Bharathi; A, Asifa Shaz; AG, Anjana (Journal of Pharmacy Practice and Community Medicine)
Dengue shock syndrome is the terrible form of dengue infection. The people with defective immune system or with persistent dengue infection are more likely to develop shock syndrome at higher risk. Initial warning sign of severe dengue is gradual fall in body temperature, it is wrong sign of recovery from infection but the patient should feel retrieval from illness. This form of dengue, progressively cause complication in multiple organ and rapidly leads to death. To avoid this life-threatening condition such patient must need admission in hospital to manage this ailment. Early identification and treatment may reduce mortality in patient with dengue shock syndrome.
Keywords: Severe dengue; Phases of dengue; Plasma leakage; Shock; Platelet transfusion